IMPLEMENTATION MONITORING RAW MATERIAL OF RUBBER PT.PERINDUSTRIAN DAN PERDAGANGAN BANGKINANG PEKANBARU - Doni Zuhri Suntago; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Monitoring of inventory and procurement of raw materials is the main thing that must be done by a company in order to meet the needs of the desired material . In the procurement and supply of raw materials in the company of accuracy needed to see if the raw materials both in terms of quality and quantity .The population in this study is the head of the company and employees of PT . Industry and Trade Bangkinang Pekanbaru . The company leader is being key informant , while the purchasing department , production department and the warehouse is taken as the research sample , which is taken proportional random sampling is sampling by taking 50 % of the population in every part of the company that will be investigated and then used respondents in this study .Based on the results of previous studies , the authors can draw conclusions and suggestions . The conclusion of this study , the implementation of the inventory control of raw material of rubber on the PT . Industry and trade Bangkinang Pekanbaru has been quite good , it can be seen from the overall summary of respondents' answers .Keywords : monitoring , inventory , productio